2011
DOI: 10.1186/2041-7136-1-17
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and livestock mortality in communally used pastoral areas: the impact of the 2005-2006 drought on livestock mortality in Maasailand

Abstract: There is consensus that pastoral mobility is beneficial for both pastoralists and the environment. However, rapid change arising from multiple factors, including landscape fragmentation, sedentarization, and demographic drivers might affect the effectiveness of this pastoral coping strategy in times of drought. We investigate livestock mortality rates following the 2005 drought in four areas in Maasailand: the Maasai Mara, the Kitengela plains, the Amboseli, and the Simanjiro plains. The main aim was to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 24 publications
1
62
0
1
Order By: Relevance
“…The recent discovery of underground water sources is, however, widely viewed by respondents as the panacea that will end Turkana's chronic water shortage. In general, the observations made by the respondents in this study confirm the findings by Nkedianye et al (2011) that the increasing frequency and intensity of drought events are negatively impacting pastoral livelihoods and ecosystems. …”
Section: Impacts Of Drought As Perceived By the Householdssupporting
confidence: 77%
See 3 more Smart Citations
“…The recent discovery of underground water sources is, however, widely viewed by respondents as the panacea that will end Turkana's chronic water shortage. In general, the observations made by the respondents in this study confirm the findings by Nkedianye et al (2011) that the increasing frequency and intensity of drought events are negatively impacting pastoral livelihoods and ecosystems. …”
Section: Impacts Of Drought As Perceived By the Householdssupporting
confidence: 77%
“…In the ASALs, for example, frequent droughts are associated with the deterioration of livestock condition, increased incidences of certain diseases and livestock deaths, altered herd structure, and a collapse of livestock markets (Speranza 2010). As a result of frequent droughts, a high level of livestock mortality has become a norm in the study area ( Huho and Mugalavi (2010) and Nkedianye et al (2011) reported a positive correlation between drought severity and the magnitude of livestock losses in northern Kenya. Further discussions with the key informants revealed that increased incidence of livestock disease was also partly associated with drought in Turkana.…”
Section: Impacts Of Drought As Perceived By the Householdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bårdsen and Tveraa 2012). Evidence from Africa indicates that while mobility may be beneficial for pastoralists leaving drought affected areas, it is not so beneficial for pastoralists already inhabiting areas used as drought refuges: a higher stocking density (as a result of influx of pastoralists escaping drought stricken areas) led to heightened competition for forage and subsequent starvation for resident livestock (Nkedianye et al 2011).…”
Section: Feedback: Climate Change Fragmentation and Mobilitymentioning
confidence: 99%